Natural and engineered resistance to plant viruses - Carr, John Peter; Loebenstein, G. (Gad) (Advances in virus research, 2009)
Viruses are a huge threat to agriculture. In the past, viruses used to be controlled using conventional methods such as crop rotation and destruction of the infected plants but now there are more novel ways to control them. This volume focuses on natural and engineered virus resistance, the two major strategies used for crop protection. * Contributions from leading authorities * Informs and updates on all the latest developments in the field.